The Influence of Parental Support on Adolescent Mental Health - Mulyanti, Lia; Khasanah, Umi (Jurnal Kebidanan, 2025)
During this stage adolescents face many challenges due to rapid physical changes followed by other changes. If adolescents are unable to adjust, they may experience stress. Social support is a factor that has the potential to cause stress disorders in adolescents, on the other hand social support for adolescent mental health is social support from family members, and peers can affect adolescent mental health. Family support helps adolescents develop a greater sense of balance, support during moments of helplessness and assist in the achievement of developmental tasks. Family support can be in the form of informational support, appraisal support, instrumental support and emotional support This type of research is The type of research used is analytic research. The method used is a survey method using a cross sectional approach. The samples used for research 153 people The results of the research that most parents were supportive with 99.3% and unsupportive with 0.7%. The conclusion is The conclusion of this study is that there is an influence between family support and adolescent mental health at Pondok Pesantren KH. Sahlan Rosdiji Semarang.